Pengaruh Modifikasi Agregat Halus dan Volume Foam terhadap Sifat Mekanik Beton Busa - S.T., M.T., Naifah (Jurnal Sains Riset, 2025)
Foamed concrete is a lightweight concrete produced by incorporating foam into a cement paste matrix of water and fine aggregates, forming air voids that reduce density. This study evaluates the effect of fine aggregate size and foam volume on the compressive performance of foamed concrete. Fine aggregates with sizes of 4.75 mm, 2.36 mm, and 1.18 mm were used, with target densities of 800, 1000, and 1200 kg/m³. Mix design followed the Absolute Volume Method in compliance with ASTM C29 and SNI standards. Results show that higher density mixes (1200 kg/m³) provide greater compressive strength compared to lower densities (800 kg/m³). Reduced foam volume enhances matrix compactness, thus improving strength. Curing conditions also influence mechanical properties, with the 1200 kg/m³ mix achieving the highest shear strength. After 28 days, water curing yielded modulus of elasticity values close to or slightly lower than those under air-dried conditions.